Typology of Governance: Case Study of the Evolution of National Climate Change Policy - Sinaga, Jona Bungaran Basuki (Universitas Sultan Ageng Tirtayasa, 2024)
Indonesia is the second largest producer of greenhouse gases in the world and is a country vulnerable to the impacts of climate change. Serious efforts and policies have been undertaken to address climate change. Although there is much research about climate governance in Indonesia, there is limited understanding of how and why governance arrangements change over time, and there is still a lack of a clear conceptual framework for distinguishing governance models and studying the evolution of governance. This research aims to describe the typological framework of climate change governance policy evolution in the policy dimension. The research design uses a qualitative approach with content analysis techniques. The data sources in this research are only secondary data. This study uses the policy dimension governance framework to examine the typology of the evolution of Indonesia's national climate change policies since 1972. The findings show that Indonesia has implemented various national policy instruments since the 1990s to address climate change in different policy dimension governance typologies. The findings also show that the typology of climate change governance in Indonesia has shifted from voluntarism to coercion and targeting.